Phylogeography of Pteronotropis signipinnis, P. euryzonus, and the P. hypselopterus Complex (Teleostei: Cypriniformes), with Comments on Diversity and History of the Gulf and Atlantic Coastal Streams. (31st May 2015) - Mayden, Richard L.; Allen, Jason
Abstract : The cyprinid genus Pteronotropis is endemic to southeastern Gulf of Mexico and Atlantic Ocean of North America. Never before has the genus been demonstrated to be monophyletic. We investigate both the phylogenetic relationships and the phylogeography of some species in the genus using mitochondrial ND2 sequences. In no analysis is the genus resolved as monophyletic if Notropis harperi is not included in the genus. Biogeographic and phylogeographic evaluations are conducted with Pteronotropis, including P. signipinnis, P. euryzonus, and the P. hypselopterus complex. Patterns of relationships and population genetic analyses support divergences within multiple clades both at the species level and within species that are tied to abiotic changes in the region. Replicated patterns across clades are observed, as well as patterns previously found in other taxa. Pteronotropis hypselopterus is likely not a natural grouping as populations from some drainages form clades more closely related to other species of the genus. The general patterns of relationships indicate likely cryptic species not currently recognized. Finally, the patterns of species relationships and clades and population structuring within species serve as another example of replicated divergences in the biodiversity east and west of the Mobile Bay.